2022
DOI: 10.21041/ra.v12i3.594
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibras de celulose (NFC) como reforço de matrizes cimentícias: revisão sistemática da literatura

Abstract: O objetivo deste estudo é realizar uma revisão sistemática da literatura dos últimos cinco anos sobre o uso de nanofibras de celulose (NFC) em compósitos cimentícios. São apresentadas as principais formas de produção e dispersão, com destaque para o efeito sobre o comportamento dos materiais à base de cimento. O estudo considerou a influência das NFC nas propriedades no estado fresco e endurecido: reologia, hidratação, resistência à compressão, resistência à flexão, energia de fratura, entre outras. As NFC têm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Cellulose nanofibers can be used as a composite material, and, in particular, cellulose nanofiber composite resins have attracted a great deal of attention [ 6 , 7 ]. Cellulose nanofiber composite resins have shown better mechanical performance than the base polymer, making them suitable for various industries [ 3 , 8 ], such as the automotive [ 9 ], packaging [ 10 ], medical implant [ 11 ], electronics [ 12 , 13 , 14 , 15 ], building material [ 16 ], and paper industries [ 17 ]. However, very few studies have reported on composite materials with cellulose added to metal-based matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanofibers can be used as a composite material, and, in particular, cellulose nanofiber composite resins have attracted a great deal of attention [ 6 , 7 ]. Cellulose nanofiber composite resins have shown better mechanical performance than the base polymer, making them suitable for various industries [ 3 , 8 ], such as the automotive [ 9 ], packaging [ 10 ], medical implant [ 11 ], electronics [ 12 , 13 , 14 , 15 ], building material [ 16 ], and paper industries [ 17 ]. However, very few studies have reported on composite materials with cellulose added to metal-based matrices.…”
Section: Introductionmentioning
confidence: 99%